Development and wear resistance evaluation of epoxy resin composite reinforced with cow horn and corn cob. (16th February 2021) - Ariwoola, Olamide Emmanuel; Taiwo, John Adeola; Abioye, Taiwo Ebenezer; Oladele, Isiaka Oluwole
In this work, epoxy resin composites reinforced with varying compositions (0 wt.%-20 wt.%) of cow horn (CH) and corn cob (CC) particles were developed. The microstructure, hardness and wear resistance of the composites were investigated. The microstructure analysis revealed that the CC appeared to be fibre-like while the CH appeared as particles in the epoxy resin matrix. The particles content and distribution were enhanced as the CH composition in the composites increased. Compared to the unreinforced sample, the composite started showing improvement in hardness at 6 wt.% CH content (10.1 HV). This increased with increase in CH content and maximum was found at 20 wt.% CH (18.6 HV). CC additions have no considerable influence on the composite hardness. The entire composites exhibited lower wear rate compared with the epoxy resin sample. The least wear rate was found at 20 wt.% CH. CH reinforcement enhanced the composite wear properties than the CC.